THE DIGITAL NATIVE VOICES IN A FLIPPED CLASSROOM - Atsani Wulansari; Widya Ratna Kusumaningrum (Jurnal Sosioteknologi, 2020)
The growing of technology has invited the traditional pedagogical method supporters to integrate technology in education. This paper investigates the student perceptions as digital natives on the application of flipped classroom model. The flipped classroom employs lecturing video as homework and group discussion as classroom activities. The participants in this study were 120 students aged 19-20 years old who were born as millennial generation and had the experience of the flipped classroom model. Using a descriptive qualitative, the issue was observed and investigated. To elicit the student perceptions, this study used an open-ended questionnaire to investigate these students' opinions and attitudes toward the implementation of the model and its advantages and disadvantages. As the result shows, that flipped classroom gives more benefits over the drawbacks. The implementation of flipped classroom has attractively motivated students to be engaged in the classroom activity. The students perceive that the flipped classroom model has positively transformed their attitude and behavior in learning and flipped into a new way of learning. They argue that the procedural steps in flipped classroom model such as video observation and discussion help them understand the materials better and to be an independent learner. To conclude, the implementation of flipped classroom model gains the students' positive views over the negative perceptions.